Fatores da produção de milho em função da adubação orgânica e de Trichoderma spp. - Durigon, Miria Rosa (2012)
The expansion of area under maize (Zea mays L.), and the use of no-till without a proper crop rotation have increased the incidence of stalk rot on this crop, due to the survival of this disease-causing pathogens (Fusarium spp., Diplodia spp., Colletotrichum graminicola, among others) in soil and crop residues. Fertilization has shown positive effect on the crop, but little is known about its relation to these pathogens and the organisms that control them. The objective of this study was to evaluate the effect of short and long-term of organic and mineral fertilizers and the effect of treatment of corn seeds with Trichoderma spp. Persson on the population of total fungi, Fusarium spp., and Trichoderma spp. in the soil and the production of dry matter (DM), accumulation of nitrogen (N), phosphorus (P) and potassium (K) in the tissue and grains, the incidence of stalk rot and corn yield. The experiment was conducted at the experimental area of the Soils Department, Federal University of Santa Maria, which has a history of six years application of organic and mineral fertilizers, and consisted in a factorial 5 (fertilization treatments) X 2 (seeds treatment) with split-plot in strips, using the randomized block design. The fertilization treatments (pig slurry; swine deep bedding; cattle slurry; mineral fertilizer; control treatment) were applied to the plots and the seeds treatment (with and without Trichoderma spp.) in the subplots (strips). It was used the hybrid Pioneer ® 30F53 Y, with 45 cm row spacing and final population of 78,000 plants per hectare. Soil samples were collected before application of treatments, for chemical analysis, and before and after, to characterize the soil fungal population. In the laboratory, dilution of samples and quantification of the fungi present was performed. At the flowering stage, three corn plants per subplot were collected for the assessment of DM production and nutrient accumulation in the tissue. At physiological maturity stage, the incidence of stalk rot was assessed, and the ears of corn harvested for productivity assessment. Nutrient content in corn kernels was also determined. The organic fertilizers pig slurry and swine deep bedding, in the long-term, increased population of Fusarium spp. in the soil. The organic and mineral fertilizers increased the production of DM and productivity of corn. Trichoderma spp. increased the production of DM of corn, but had no reflection on productivity. Both factors increased the incidence of stalk rot in corn. The swine deep bedding and cattle slurry increased the content of P and K in the tissue of corn plants. It is concluded that: the organic fertilizers can be used to increase the production of DM and productivity of corn and; Trichoderma spp. can be used if the objective is greater DM production.